Frozen II. Anna, Elsa, and the secret river - Rosenbaum, Andria Warmflash, 1958- (Los Angeles : Disney Press, 2019)
A young Elsa and Anna follow a river in search of the answer behind Anna's magic powers.
2.0
K-3
Keywords: Rivers -- Juvenile fiction; Sisters -- Juvenile fiction; Magic -- Juvenile fiction; Rivers -- Fiction; Sisters -- Fiction; Magic -- Fiction; Fantasy; Picture books; Fantasy fiction